NAVIGATING JUSTICE AND LEGAL EQUILIBRIUM IN AUTOMATIC PRICING ALGORITHMS: A CROSS BORDER LEGAL APPROACH - Eviani, Nanda Yuniza; Yunus, Ahsan; Hafizhah, Noor Ashma; Irwansyah, Irwansyah (Universitas Lampung, 2024)
Automatic pricing algorithms with artificial intelligence (AI) technology in e-commerce have a significant impact on the running of the industry. This creates benefits as well as reaps polemics. Discrimination against consumers is one of them. For this reason, comprehensive treatment is needed to prevent negative impressions from occurring and can lead to the creation of justice and fairness. This research is normative qualitative research with the support of case and comparison approaches. The research results show that the algorithm uses AI to set prices based on market factors, production costs, and competition, providing price flexibility, price relevance, and increased business efficiency. Positive impacts include increased efficiency, price relevance, and consumer reach, while negative impacts involve the risk of discrimination and supervisory difficulties. Regulation and supervision are needed to maintain justice and legal balance. Unfair competitive practices, such as sudden price fluctuations, need to be monitored. Explicit regulations are needed to address the gap between AI developments and the existing legal framework. The implementation of automatic pricing algorithms must pay attention to aspects of justice and legal balance.